2001
DOI: 10.1159/000047795
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ryanodine Binding to Sarcoplasmic Reticulum Vesicles of Cardiac Muscle by Zn<sup>2+</sup> Ions

Abstract: Using the assay of [3H]ryanodine binding to the sarcoplasmic reticulum, the effect of Zn2+ on ryanodine receptors (RyRs) of cardiac muscle was investigated. There was no obvious change in the binding at [Zn2+]f of less than 0.2 µM. However, a decrease of the binding became significant with raising [Zn2+]f to 0.5 µM. The inhibitory effect of Zn2+ was [Zn2+]f-dependent, with IC50/ZnI of 2.1±0.4 µM (mean±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…It is indicated that caffeine contracture of smooth muscle and skeletal muscle was differentially affected by Zn 2+ . The present result seems to be consistent with the differential effect of Zn 2+ on ryanodine binding to the SR vesicles of skeletal muscle and cardiac muscle [6,7]. However, there are many sites of action of Zn 2+ , which may be involved in modulating the contraction of muscle cells [2][3][4][5].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is indicated that caffeine contracture of smooth muscle and skeletal muscle was differentially affected by Zn 2+ . The present result seems to be consistent with the differential effect of Zn 2+ on ryanodine binding to the SR vesicles of skeletal muscle and cardiac muscle [6,7]. However, there are many sites of action of Zn 2+ , which may be involved in modulating the contraction of muscle cells [2][3][4][5].…”
Section: Discussionsupporting
confidence: 88%
“…The decrease of the binding became obvious with [Zn 2+ ] of more than 1 µM [6]. In contrast, the effect of Zn 2+ in cardiac muscle was monophasic [7]. Ryanodine binding to the SR vesicles of cardiac muscle could not be changed by low [Zn 2+ ], while a significant decrease of the binding occurred with raising [Zn 2+ ] to 0.5 µM.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Under the circumstances present at »1420 s, when external Zn is non-existent and internal Zn is relatively high (»10 nM), inward calcium current may have been inhibited by intracellular rather than extracellular Zn 2+ (Atar et al, 1995;Turan, 2003). It is also possible that high [Zn 2+ ] i blocked the release of SR Ca 2+ , perhaps by inhibiting Ca 2+ -induced opening of SR Ca 2+ release channels (Wang et al, 2001). Based on our X-ray Xuorescence images and our data from Xuorescence microscopy, we speculate that there exist signiWcant internal stores of Zn 2+ in organelles, probably in the SR, and that these stores of Zn 2+ modulate Ca 2+ regulation.…”
Section: Cardiomyocyte [Zn 2+ ] Imentioning
confidence: 99%
“…These data demonstrate that external Zn 2+ inhibits systolic characteristics of cardiomyocyte [Ca 2+ ] i dynamics. The inhibition of calcium induced calcium release from the SR by external Zn 2+ may occur via the reduction in Ca 2+ inXux through sarcolemmal calcium channels (Atar et al, 1995;Turan, 2003) or via reducing the probability of opening SR Ca 2+ release channels (Wang et al, 2001). Table 1 Mean and standard errors (SEM) of measured concentrations ( g/cm 2 for P-K and ng/cm 2 for Ca-Zn) of nine elements in large (not less than 100 m 2 ) regions of interests selected in six diVerent intact rat cardiomyocytes Approximated concentrations (ppm and mM) were calculated after assuming sample width of 10 m and atomic weights shown.…”
Section: Cardiomyocyte [Ca 2+ ] I In Response To [Zn 2+ ] Imentioning
confidence: 99%